Nitrogen Removal and Sludge Reduction in Anoxic-Aerobic Sequencing Batch Reactor with Alkaline-H2O2 Disintegration - Gurtekin, Engin (Sciendo, 2022)
In this study, alkaline-H2O2 sludge disintegration was combined with anoxic-aerobic sequencing batch reactor (SBR). The carbon obtained by alkaline-H2O2 sludge disintegration was used in the denitrification process and sludge reduction was achieved in the SBR process. In the SBR process, a 9 % increase in nitrogen removal efficiency was achieved with the improvement in the denitrification process. A sludge reduction efficiency of 43 % was obtained in the SBR process with alkaline-H2O2 sludge disintegration. A synergistic effect was obtained in the combination of alkaline and H2O2 methods and the sludge reduction increased by 8 %. By combining sludge disintegration into the SBR process, it is possible to reduce the amount of sludge formed, which is an important environmental problem, and to provide carbon source for the denitrification process.
Keywords: sludge disintegration; alkaline-H2O2; nitrogen removal; sequencing batch reactor